2015
DOI: 10.1136/bmjopen-2015-009015
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tiotropium in patients switching from HandiHaler to Respimat in the TIOSPIR trial

Abstract: ObjectivesThis post hoc analysis of TIOtropium Safety and Performance In Respimat (TIOSPIR) evaluated safety and exacerbation efficacy in patients with stable (≥2 months) use of tiotropium HandiHaler 18 µg (HH18) prior to study entry, to evaluate whether there was a difference in risk for patients who switched from HH18 to tiotropium Respimat 2.5 µg (R2.5) or 5 µg (R5).SettingTIOSPIR (n=17 135) was an international, Phase IIIb/IV, randomised, double-blind, parallel-group, event-driven trial.ParticipantsPatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Tiotropium bromide SMI provides a solution form of tiotropium bromide 55 that is efficacious at lower doses compared with the tiotropium bromide HandiHaler ® (Boehringer Ingelheim). 56 In patients with COPD, tiotropium SMI improved lung function, health-related quality of life, and dyspnea, reduced acute exacerbations of COPD, and was as effective and safe as the tiotropium HandiHaler 57 , 58 Tiotropium is generally well tolerated in patients with COPD, but antimuscarinic side effects (eg, dry mouth) are among the most commonly reported adverse events. 59 …”
Section: Nebulized Pharmacologic Therapymentioning
confidence: 99%
“…Tiotropium bromide SMI provides a solution form of tiotropium bromide 55 that is efficacious at lower doses compared with the tiotropium bromide HandiHaler ® (Boehringer Ingelheim). 56 In patients with COPD, tiotropium SMI improved lung function, health-related quality of life, and dyspnea, reduced acute exacerbations of COPD, and was as effective and safe as the tiotropium HandiHaler 57 , 58 Tiotropium is generally well tolerated in patients with COPD, but antimuscarinic side effects (eg, dry mouth) are among the most commonly reported adverse events. 59 …”
Section: Nebulized Pharmacologic Therapymentioning
confidence: 99%
“…An analysis of patients treated with tiotropium HandiHaler® 18 μg at TIOSPIR® baseline, and who were randomized and subsequently received tiotropium Respimat® 5 μg during the study, showed that they had similar risks for all-cause mortality (HR 0.79; 95% CI 0.58–1.07), fatal MACE (HR 0.67; 95% CI 0.33–1.34), MACE (HR 0.69; 95% 0.44–1.08) and exacerbations (HR 0.96; 95% CI 0.86−1.08) as patients who continued to be treated with tiotropium HandiHaler® 18 μg [ 27 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…For physicians who may be considering whether patients are suitable candidates to switch from tiotropium HandiHaler® to tiotropium Respimat®, TIOSPIR® data show that in patients who switched from tiotropium HandiHaler® to tiotropium Respimat®, mortality, cardiac safety and exacerbation outcomes were similar to those who remained on tiotropium HandiHaler® [ 27 , 29 ]. From the patient’s perspective, studies have suggested that they find it easy to switch from tiotropium HandiHaler® to tiotropium Respimat®, and have reported high levels of preference for, and adherence to, tiotropium Respimat® [ 61 – 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TIOSPIR study (TIOtropium Safety and Performance In Respimat) also showed that different formulations of tiotropium (Respimat at a dose of 2.5 or 5 μg and HandiHaler at 18 μg; both from Boehringer Ingelheim GmbH) had a similar risk of death [30]. Furthermore, the risk of exacerbation and major adverse cardiovascular events did not differ significantly among the three treatment groups [30], or upon switching patients from tiotropium HandiHaler to tiotropium Respimat [31].…”
Section: Labas and Lamas In Copdmentioning
confidence: 98%